Bacterial diversity of Moutai‐flavour Daqu based on high‐throughput sequencing method. Issue 1 (28th March 2017) - Wang, Xiaodan; Ban, Shidong; Hu, Baodong; Qiu, Shuyi; Zhou, Hongxiang
Abstract : In this study, we investigated the bacterial diversity of Moutai Daqu, Zhongxing Daqu and Zhengjiu Daqu from Guizhou Province of China by high‐throughput sequencing method. Sequencing results showed that 35 bacterial families were detected in the three Daqu samples. More interestingly, Sporolactobacillaceae, Streptomycetaceae, Pseudomonadaceae, Actinopolysporaceae, Caulobacteraceae, Pseudonocardiaceae, Nocardiaceae and Methlobacteriaceae were reported foe the first time in Moutai‐flavour Daqu using high‐throughput sequencing method. In particular, Thermoactinomycetaceae and Bacillaceae were demonstrated to be the common dominant bacteria in the three samples. These new data offer a more complete view of comprehensive of high‐throughput sequencing method to understand bacteria diversity of Moutai‐flavour Daqu. Copyright © 2017 The Institute of Brewing & Distilling